The analysis of the influence of the thermal shocks on acoustic emission signal generated in cordierite ceramics - RANACHOWSKI, Z.; RANACHOWSKI, P. (Archives of Acoustics, 2000)
The paper describes a raw materials composition and manufacturing technology of cordierite material, applied to manufacturing of welding backing strips. The resistance of the cordierite specimens to thermal shock within the range of 150–320°C was analysed. Shocked samples, submitted to three - point mechanical stress, have been investigated by acoustic emission method. The results let the authors to conclude that there is a correlation between the Acoustic Emission (AE) signals parameter, describing the AE activity during the loading and the stage of material degradation caused by the applied thermal shock.